Dianetics [soundrecording] : the evolution of a science - Hubbard, L. Ron [ (La Fayette Ron)] , 1911-1986; Sherr, Lloyd (Golden Era Productions, 2007)
Reveals L. Ron Hubbard's own story of how he discovered the Reactive Mind and the technology to conquer it